The Effectiveness of Parents Income Factor, Genetic Factor and Parents Behavior to Stunting at Sukamaju Village, Sako District, Palembang City - Turania, Konita; Islamy, Diah Putri (FIA UB, 2020)
This study aims to examine the effectiveness of parents income factor between genetic factor and parents behavior to stunting at Sukamaju Village, Sako District, Palembang City. Stunting problems describe very bad nutritional problems, influenced by the condition of the mother or expectant mothers, fetal period, and infant or under-five years, including illness suffered during childhood. Analysis of the percentage or coefficient of income levels, genetic factors and the behavior of the elderly in children under five with stunting cases. The results show 39 children under five who experienced stunting out of 100 respondents under five who were studied. The level of income, genetic factors and parental behavior relate to incidence of stunting among toddlers in Sukamaju village